Right to Social Influence and Duty of Responsibility - Shaverdyan, Gayane (Bulletin of Yerevan University E: Philosophy, Psychology, 2014)
The author draws parallels between white/black magic and positive/negative social influence. It is shown, that for protection against the impact, the awareness of the aims and intentions of the subject of influence are central. This determines the freedom to accept or reject content of the influence. In other words, the motivation component of social influence is more important than its information and communication parties.
Keywords: social influence, manipulation, motivation, intellect, empathy